Thermal Strain and Magnetization Studies of the Ferromagnetic Heusler Shape Memory Alloys Ni2MnGa and the Effect of Selective Substitution in 3d Elements on the Structural and Magnetic Phase - Sakon, T.; Nagashio, H.; Sasaki, K.; Susuga, S.; Numakura, D.; Abe, M.; Endo, K.; Yamashita, S.; Nojiri, H.; Kanomata, T. (IntechOpen, 2013)
None